Upaya Meningkatkan Prestasi Belajar Siswa dengan Media Video Pembelajaran di SMK S Terpadu Gema Nusantara - Miza Jonika Sari; Lisda Herawati (Kampus Akademik Publiser, 2024)
This study aims to improve student learning achievement through the use of learning video media in the subject of Basic Human Needs in class XI Nursing 3 Integrated SMK S Gema Nusantara Bukittinggi. The background of this study is the low student learning outcomes in online learning, where most students have difficulty understanding material that is only delivered through textbooks. This study used the Classroom Action Research (PTK) method which was carried out in three cycles. Each cycle consists of planning, action, observation, and reflection stages. The instruments used include lesson plans, teaching materials, LKPD, evaluation tests, and student questionnaires. Data were collected through learning outcome tests, student activity observations, and score documentation, then analyzed descriptively quantitatively. The results showed an increase in student learning achievement in each cycle. In cycle I, learning completeness only reached 74.17%, increased to 77.30% in cycle II, and reached 88.33% in cycle III. Thus, learning video media proved to be effective in improving student learning achievement.